Work and well-being in teams - Nielsen, Karina (2003)
This thesis examines work and well-being in relationship to teamwork in two organisations employing professionals; one organising work in Japanese style teams and one with self-managing work teams. It offers a critique of current research on employee well-being in teams and outlines some ways forward for filling in the gaps in existing research.